THE PITTSBURGH FATIGABILITY SCALE: VALIDATION OF THE MENTAL SUBSCALE IN THE LONG LIFE FAMILY STUDY - Renner, Sharon W (Innov Aging, 2019)
We previously validated the physical, but not the mental subscale of the Pittsburgh Fatigability Scale (PFS). Thus, we aimed to validate the PFS mental subscale in 1,738 individuals aged ≥60 from the Long Life Family Study (55.5% female, age 74.8±11.1 years, PFS mental score 7.1±10.1, range 0-50). Confirmatory factor analysis with promax rotation showed all 10 items loaded on two factors: social and physical activities (SRMR=0.07, RMSEA=0.13, CFI=0.90). PFS mental score had strong internal consistency (Cronbach’s α=0.90) and demonstrated moderate concurrent and construct validity using Pearson correlations against measures of cognition (Trail Making A (r=0.26) and B (r=0.29) time), gait speed (r=-0.30), and the Center for Epidemiologic Studies Depression Scale (r=0.35), p<0.0001 for all. In conclusion, by accounting for self-pacing inherent in common fatigue questionnaires, the validated PFS mental subscore may be a more sensitive tool to examine perceived mental fatigability as an important contributor to cognitive and physical function.